Analysis of the Revitalization Strategy for the Development of Wamsoba Beach Tourism Area, Namrole District, South Buru Regency - Nurlatu*, Nikson; Zacharias, Tehubijuluw; Arifin, Muhammad Husni (Universitas Syiah Kuala, 2024)
Objective study This is for analyze about analysis strategy revitalization development area tour beach especially on the beach Wamsoba Subdistrict Namrole, South Buru Regency. The method used in this study is a qualitative type, namely an analysis used to describe or solve problems systematically using the SWOT analysis method. The results of this study indicate several strategies that need to be carried out by Service Tourist and District Culture. Among them is are arranging and repairing damaged facilities, keeping beaches/objects clean, providing annual operational costs, coordinating with local governments in terms of budget availability. Based on the SWOT analysis, build network cooperation with stakeholders so that the management process area beach Wamsoba. Organize And repair damaged facilities, look after beach/object in order to stay clean, provide cost operational in every years, coordinate with government area in matter availability budget, do promotion about beauty tour Beach Wamsoba, improvement the quality of tourism human resources must own certification tourism And make advertisement promotion tour.